Effects of industrial concentration : a cross-section analysis for the Common Market - Phlips, Louis; Commission of the European Communities (Amsterdam : North-Holland Pub. Co., 1971)
A report written for the Commission of the European Commission. It is an empirical analysis of some economic effects of industrial concentration covering the entire manufacturing industry of some European Economic Commission (EEC) countries. It focuses on the econometric relationships existing between industrial concentration and some indicators of economic performance.
A revised and enlarged version of a report written for the Commission of the European Communities.
Includes bibliographical references.
lje 6/4/17
Loans
Keywords: Big business; Manufacturing; Industrial concentration; Industries